Morphological and Molecular Characterisation of Water Lily (Family: Nymphaeaceae) in UNIMAS Lake East Campus - Natasha Arina, Binti Mohd Izham (Universiti Malaysia Sarawak, (UNIMAS), 2014)
Water lilies are aquatic angiosperms in the Family Nymphaeaceae. They are important ornamental plants that enhance the beauty of ponds and lakes. Several studies on water lilies in Sarawak had been carried out on ecological aspects, but there is limited number of molecular data on water lilies in Malaysia available in the GenBank. This study is designed to sequence the internal transcribed spacer (ITS) regions of nuclear ribosomal DNA from the water lilies sampled from Universiti Malaysia Sarawak (UNIMAS) Lake, East Campus. A total of 11 water lilies were subjected to identification based on morphological characteristics. In addition, for molecular work, the total genomic DNA was extracted from the flowers and leaves using modified CTAB method followed by Polymerase Chain Reaction to amplify 730 bp ITS gene, DNA sequencing and data analysis. In this study, there were three species of water lily found in UNIMAS Lake identified as Nymphaea capensis, N. lotus and N. pubescens based on combination of morphological data and ITS gene sequence. N. capensis1 and N. capensis2 have low genetic divergent (0% - 0.9%) which suggesting intraspecific variations. N. capensis and N. lotus have 30.7 % of genetic divergent whereas N. lotus and N. pubescens have genetic divergent value of 5.5 %. N. lotus is monophyletic with high bootstrap value, 98% in NJ tree and 97% in MP tree. N. capensis has bootstrap value of 99% in NJ tree and 100% in MP tree which indicates that the species is monophyletic. N. pubescens is also monophyletic with 100% bootstrap value in both NJ and MP tree.